إدارة وتسيير الأملاك الوقفية في الجزائر - ـــ مداني عادل (جامعة المسيلة, 2020)
الوقف يعد من بين أهم الأملاك العقارية في الجزائر لهذا وضع له المشرع منظومة قانونية محكمة لتنظيمه وتسييره وإدارته من خلال القوانين التي سنها له تفعيلا لدوره واسترجاعا لمكانته. ومع ذلك فإن المشرع رغم ما أحاطه من سياج محكم في تنظيم أحكام الوقف إلا أنه بقي يشوبه عدة نقائض؛ لذلك لابد عليه أن يسد الثغرات القانونية حتى يطبق هذا النظام على أسس قانونية متينة بدعمه بما يوازيه من القوانين المرتبطة - العقارية و المالية والمدنية والتجارية والجنائية - بتعديلها ووضع مساحة فيها لأحكام الوقف من اجل الوصول إلى سبل مثلى في تسيير وإدارة الوقف. The endowment is considered one of the most important real estate properties in Algeria. That is why the legislator has established a legal system for him to organize, manage and administer it through laws enacted for him in order to activate his role and restore his status. Nevertheless, the legislator, despite the tight fence surrounding it in organizing the provisions of the endowment, remained tainted by several contradictions. Therefore, it must fill the legal loopholes in order to implement this system on solid legal foundations by supporting it with its equivalent related laws - real estate, financial, civil, commercial and criminal - by amending them and setting up space in it for the provisions of the endowment in order to reach optimal ways in the management and administration of the endowment. Key words: endowment - management and administration - endowment properties - laws
Keywords: : endowment - management and administration - endowment properties